2022
DOI: 10.1186/s42077-021-00207-w
|View full text |Cite
|
Sign up to set email alerts
|

Inadvertent severe hypercapnia during general anesthesia: drop-in oxygen saturation or electrocardiography changes; which one warns us earlier?

Abstract: Background During general anesthesia especially when the nurse or anesthesiologist forgets to change manual to controlled mode after successful endotracheal intubation, capnography shows End-tidal Co2 above 20 mmHg after checking the place of the tracheal tube and will remain on the screen permanently. In this scenario, the patient receives a high concentration of oxygen, and Spo2 (oxygen saturation) does not drop for a long time which is too late to intervene. It has been all-time questionable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In the present study, longer durations of anesthesia resulted in an increase in lung injury. Emphysema, atelectasis, and inflammatory cell infiltration showed in all the pigs, but the pig that died at 48h showed a higher level of ETCO2, which has been associated with inadequate ventilation or decreased CO2 elimination during anesthesia (Peltekova et al 2010;Solhpour et al 2022), which led to respiratory failure in our study. A study of patients who showed postoperative pulmonary complications (PPCs) acquired during prolonged (≥24h) anesthesia with mechanical ventilation (Pedersen et al 1992) found that the most frequent lesions on the PPCs were pathologies of atelectasis and pneumonia, which presented on 2.6% and 50% of the subjects, respectively.…”
Section: Discussionmentioning
confidence: 56%
“…In the present study, longer durations of anesthesia resulted in an increase in lung injury. Emphysema, atelectasis, and inflammatory cell infiltration showed in all the pigs, but the pig that died at 48h showed a higher level of ETCO2, which has been associated with inadequate ventilation or decreased CO2 elimination during anesthesia (Peltekova et al 2010;Solhpour et al 2022), which led to respiratory failure in our study. A study of patients who showed postoperative pulmonary complications (PPCs) acquired during prolonged (≥24h) anesthesia with mechanical ventilation (Pedersen et al 1992) found that the most frequent lesions on the PPCs were pathologies of atelectasis and pneumonia, which presented on 2.6% and 50% of the subjects, respectively.…”
Section: Discussionmentioning
confidence: 56%